Influencia de la violencia de género en el área emocional en una joven de 19 años del cantón Ventanas - Guerra León, Jennifer Yosnabeth (2023)
Gender violence refers to any act of gender-based violence, which is specifically directed towards women because of their gender. It can include physical, psychological, sexual, economic and emotional violence. This is a common and widespread problem around the world that affects women of all ages, but young women are especially vulnerable. Serious consequences can result from gender-based violence, including physical and emotional injuries, mental health disorders, social isolation, loss of self-esteem and, in extreme cases, death. For this reason, it is essential to address the underlying causes of gender-based violence and ensure victims' access to resources and support to break the cycle of abuse and empower young women to live lives free of violence. From this perspective, the purpose of this research is to exhaustively examine the phenomenon of gender violence, focusing especially on the case study that focuses on evaluating how gender violence influences the emotional area of a 19-year-old girl who she resides in the Ventanas canton. This analysis is based on the bibliographic review of the components related to the topic, as well as on previous research that addresses issues linked to the problem that arises. These resources support the theoretical foundation of the research. The methodology applied in the study is a mixed approach and descriptive method. The results indicate that the different attacks have had an impact on the patient's emotional area. In summary, gender violence has a significant impact on the emotional area, which affects a person's ability to function effectively in various areas of their daily life and can also lead to mental health problems.